2012
DOI: 10.1111/j.1468-3148.2012.00698.x
|View full text |Cite
|
Sign up to set email alerts
|

Can you Know me Better? An Exploratory Study Combining Behavioural and Physiological Measurements for an Objective Assessment of Sensory Responsiveness in a Child with Profound Intellectual and Multiple Disabilities

Abstract: Obtained data, although preliminary, suggest that combining behavioural and physiological measurements may constitute a useful resource for assessing the actual responsiveness of individuals with PIMD. With such a resource, people close to these individuals could fine tune their interventions and guarantee their well-being.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…Because of the varying alertness levels and possible slower pace of information processing in people with multiple disabilities (Munde et al, 2012), it might be very important to provide them with the time and opportunity to process the interactive stimuli and respond to them. In previous research, responses often only emerged after a minimum of 3 seconds (Lima et al, 2012;Neerinckx, Vos, Van den Noortgate, & Maes, 2014;Vos et al, 2013), while further initiatives were only registered after 5 seconds (Neerinckx et al, 2014;Neerinckx, 2015). For this reason, we also calculated the corrected dynamic Jaccards for a lagged 5-second window (i.e.…”
Section: Discussionmentioning
confidence: 82%
“…Because of the varying alertness levels and possible slower pace of information processing in people with multiple disabilities (Munde et al, 2012), it might be very important to provide them with the time and opportunity to process the interactive stimuli and respond to them. In previous research, responses often only emerged after a minimum of 3 seconds (Lima et al, 2012;Neerinckx, Vos, Van den Noortgate, & Maes, 2014;Vos et al, 2013), while further initiatives were only registered after 5 seconds (Neerinckx et al, 2014;Neerinckx, 2015). For this reason, we also calculated the corrected dynamic Jaccards for a lagged 5-second window (i.e.…”
Section: Discussionmentioning
confidence: 82%
“…It has been suggested that children with PIMD may indicate pleasure or discomfort through changes in head alignment, frowning and yawning (Petitpierre et al, 2022 ). Even in children with severe disabilities, supporters may be able to interpret responses to sensory stimuli from physiological indicators such as heart rate and behaviours (Lima et al, 2012 , 2013 ). Therefore, supporters need to understand the sensory characteristics of children with PIMD and observe them from various perspectives to properly assess the changes caused by stimuli, which is likely to be the role of after‐school daycare centres involving nurses, nursery teachers, physical therapists and other professionals.…”
Section: Discussionmentioning
confidence: 99%
“…Although, Soussignan et al ( 11 ) found that odors elicit spontaneous highly legible reactions in a clinical population made up of children with severe developmental disorders and no verbal language, Lima et al ( 12 ), who presented stimuli from five different sensory modalities (visual, auditory, olfactory, gustatory, and tactile) to three children with PIMD, reported heart rate and electrodermal reactions, but no behavioral responses to two odors (vanilla, orange) and one trigeminal stimulus (vinegar) supposed to induce contrasted emotional reactions. In a second study involving a 3-year-old boy with PIMD, the same authors ( 13 ) observed no responses at all for vanilla, physiological responses to orange, and both behavioral and physiological responses to vinegar. They also reported that their participants did not exhibit observable distress or defensive responses to vinegar, a potentially aversive stimulus, but a consistent increase in motor activity, occurring simultaneously with acceleration in heart rate, that nevertheless could suggest some degree of discomfort.…”
Section: Introductionmentioning
confidence: 94%
“…The participant's teacher or educator attended the session for the safety reasons described above. The researcher who presented the stimuli to the participant opened the stick, fixed it on the clip and presented it about 2 cm in front of the participant's nose, between their nose and chin (12). Sessions were videotaped by 2 digital camcorders located 2 meters in front of the participant, one focusing on the participant's face, the other on his or her body.…”
Section: Experimenters' Operational Rolesmentioning
confidence: 99%
See 1 more Smart Citation